2014
DOI: 10.1111/1471-0528.12937
|View full text |Cite
|
Sign up to set email alerts
|

An explained variance‐based genetic risk score associated with gestational diabetes antecedent and with progression to pre‐diabetes and type 2 diabetes: a cohort study

Abstract: Objective To determine whether an explained-variance genetic risk score (GRS), with 36 single nucleotide polymorphisms (SNPs) previously associated with type 2 diabetes (T2D), is also associated with gestational diabetes mellitus (GDM), and with the progression to pre-diabetes and T2D among women with prior GDM.Design A cohort study.Setting Clinical investigation unit of Laval University, Quebec, Canada. Methods Associations between the GRS and GDM.Main outcomes measures GDM and prevalence of pre-diabetes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
(58 reference statements)
0
21
0
3
Order By: Relevance
“…Although women with a history of GDM have a greatly increased risk for T2D, not all develop T2D. Few studies have examined genetic factors of T2D in this high-risk population 10–13. A higher GRS for T2D was significantly associated with a higher risk of T2D in several studies of women with a history of GDM 10–12.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although women with a history of GDM have a greatly increased risk for T2D, not all develop T2D. Few studies have examined genetic factors of T2D in this high-risk population 10–13. A higher GRS for T2D was significantly associated with a higher risk of T2D in several studies of women with a history of GDM 10–12.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined genetic factors of T2D in this high-risk population 10–13. A higher GRS for T2D was significantly associated with a higher risk of T2D in several studies of women with a history of GDM 10–12. However, inferences from these studies are hindered by small numbers of T2D cases (n<150), and relatively short follow-up periods (<5 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AUC of the ROC curve when considering genetic polymorphisms, BMI and age was significantly greater than the AUC of the ROC curve for age and BMI alone. The authors suggested that using genetic polymorphisms in combination with traditional risk factors for type 2 diabetes was likely to be more accurate for predicting the future risk of progression to type 2 diabetes in women with prior GDM [21].…”
Section: Discussionmentioning
confidence: 99%